Panobinostat-loaded folate targeted liposomes as a promising drug delivery system for treatment of canine B-cell lymphoma - André, Ana S.; Dias, Joana N. R.; Aguiar, Sandra I.; Leonardo, Ana; Nogueira, Sara; Amaral, Joana D.; Fernandes, Célia; Gano, Lurdes; Correia, João D. G.; Cavaco, Marco; Neves, Vera; Correia, Jorge; et al. (Frontiers in Veterinary Science, 2023)
Cancer is a major public health problem with over 19 million cases reported in 2020. Similarly to humans, dogs are also largely affected by cancer, with non-Hodgkin´s lymphoma (NHL) among the most common cancers in both species. Comparative medicine has the potential to accelerate the development of new therapeutic options in oncology by leveraging commonalities between diseases affecting both humans and animals. Within this context, in the present study, we investigated the potential of panobinostat (Pan)-loaded folate-targeted PEGylated liposomes (FA-PEG-Pan-Lip) for the treatment of canine B-cell lymphoma, while contributing to new perspectives in comparative oncology. Two formulations were developed, namely: PEG-Pan-Lip and FA-PEG-Pan-Lip. Firstly, folate receptor expression in the CLBL-1 canine B-cell lymphoma cell line was assessed. After confirming receptor expression, both Pan-loaded formulations (PEG-Pan-Lip, FA-PEG-Pan-Lip) demonstrated dose-dependent inhibitory effects on CLBL-1 cell proliferation. The FA-PEG-Pan-Lip formulation (IC50= 10.9±0.03 nM) showed higher cytotoxicity than the non-targeted PEG-Pan-Lip formulation (IC50= 12.9±0.03 nM) and the free panobinostat (Pan) compound (IC50= 18.32±0.03 nM). Moreover, mechanistically, both Pan-containing formulations induced acetylation of H3 histone and apoptosis. Flow cytometry and immunofluorescence analysis of intracellular uptake of rhodamine-labelled liposome formulations in CLBL-1 cells confirmed cellular internalization of PEG-Lip and FA-PEG-Lip formulations and higher uptake profile for the latter. Biodistribution studies of both radiolabeled formulations in CD1 and SCID mice revealed a rapid clearance from the major organs and a 1.6-fold enhancement of tumor uptake at 24 hours for 111 In-FA-PEG-Pan-Lip (2.2±0.1 % ID/g of tumor) compared to 111 In-PEG-Pan-Lip formulation (1.2±0.2 % ID/g of tumor). In summary, our results provide new data validating Pan-loaded folate liposomes as a promising targeted drug delivery system for the treatment of canine B-cell lymphoma and open innovative perspectives for comparative oncology.